P348Impaired macrophage polarization in endoglin haplo-insufficiency leading to defective tissue repair is recovered by counter balance the TGFbeta pathway. (15th July 2014) - Bakker, W; Dingenouts, CKE; Lodder, K; De Vries, MR; Mager, HJ; Snijder, RJ; Westerman, CJ; Dijke, P; Quax, PH; Goumans, MJTH
Abstract: Introduction: Endoglin is a co-receptor of Transforming Growth Factorβ (TGFβ) and is crucial for the formation of new blood vessels. Endoglin-haploinsuffiency is the leading cause of the severe vascular disease Hereditary hemorrhagic telangiectasia 1 (HHT-1). The aim of this study is to investigate whether endoglin haplo-insufficiency impairs macrophage polarization towards a regenerative phenotype to induce angiogenesis and tissue repair in ischemic disease. Materials and Methods: HHT-1 was studied in Eng+/- mice and in HHT-1 patients with endoglin mutation. In Eng+/- and Eng+/+ mice, angiogenesis and tissue repair were studied by the induction of hindlimb ischemia, myocardial infarction or in matrigel plugs. Macrophage phenotypes were screened after a differentiation assay in-vitro after stimulation with GM-CSF or in tissue sections with immuno-histochemistry. Results: Angiogenic capacity was impaired in Eng+/- mice, which was associated by the infiltration of macrophages. Ischemic muscle or heart sections of Eng+/- mice showed prolonged inflammation 7 days postischemia. We can explain this by an extended polarization of bone marrow-derived monocytes (BMM) from Eng+/- mice towards pro-inflammatory macrophage (CD11b+/LY6Chi/CD206-) at the expense of regenerative macrophages. In addition, stimulation of macrophages with TGFβ resulted in the polarization of the more regenerative phenotype only in WT BMM-cultures. This TGFβ response was blunted in macrophages from Eng+/- mice, but we were able to rescue it by the inhibition of the Bone Morphogenetic Protein (BMP)-pathway (by LDN-193189). Subsequently, LDN also improved blood flow recovery and myocardial function in Eng+/- mice after hind limb ischemia and MI, respectively. Interestingly, blood monocytes from HHT-1 patients show increased number of CD14+/CD16+ monocytes, which is associated with pro-inflammatory/non-regenerative phenotype. Discussion and Conclusions: Endoglin haplo-insufficiency results in defective tissue repair due to impaired polarization of regenerative macrophages, directed by TGFβ. The defective responses were rescued by the inhibition of another TGFβ familiy member, BMP, and thereby counterbalance its pathway. These results have major implications for the treatment of HHT-1 patients, as we show the same impaired macrophage polarization.